Modelo estratégico de seguridad vial para la empresa agremiación de transportadores de Samacá para el periodo 2023-2025 (2023)
his study proposes a strategic road safety model for the company "Agremación de Transportadores de Samacá S.A.S. (ATS). The transport sector faces important challenges in terms of road safety and ATS aims to mitigate these risks. Our operating method is based on assessing company-specific risks, implementing relevant policies and procedures, and promoting a safety culture.